The Effect of Kemangi Leaf (Ocimum Basilicum) Extract in The Egg Yolk Skim Milk Diluent on The Plasma Membrane and Motility of Boerawa Goats' Sperm - Farah Ghifara Hafidha; Utomo, Budi; Soeharsono; Lestari, Tita Damayanti; Hidajati, Nove; Hermadi, Herry Agoes (Universitas Airlangga, 2025)
The purpose of this research was to determine the effect of kemangi leaf (Ocimum basilicum) extract in the egg yolk skim milk diluent on the plasma membrane and motility of Boerawa goats' sperm at room temperature. The research used fresh samples of Boerawa goat semen collected by artificial vagina. The experimental design used was a completely randomized design, divided into four treatments with six replications. The treatments were the addition of kemangi leaf extract at the levels of 0% (P0), 1% (P1), 2% (P2), and 3% (P3). Diluted semen was stored at room temperature and observed at hours 0, 1, 2, and 3. Analysis of the data using Multivariate Analysis of Variance (MANOVA), then proceed to the Duncan Test to determine significant differences between treatments. The results showed that there was no significant difference (p > 0.05) in sperm plasma membrane, but a significant difference (p < 0.05) in sperm motility was observed when kemangi leaf extract was added. However, the addition of kemangi leaf (Ocimum basilicum) extract tends to provide a better value than without it. The addition of kemangi leaf extract at a concentration of 2% yields the highest results in sperm plasma membrane integrity and sperm motility of Boerawa semen at room temperature.